Ribosomal Proteins in Ribosome Assembly - Brigitte Pertschy; Ingrid Zierler (Biomolecules)
Ribosomes are the cellular machinery responsible for translating mRNA into proteins, a process fundamental to all domains of life from bacteria to eukaryotes [...]